BENTHIC MACROFAUNA INVENTORY OF TWO SHIPWRECKS FROM PERNAMBUCO COAST, NORTHEASTERN OF BRAZIL - Amaral, F. D.; Farrapeira, C. M. R.; Lira, S. M. A.; Ramos, C. A. C. (Revista Nordestina de Zoologia, 2010)
The fauna that inhabits artificial reef environments such as shipwrecks is part of a biological community that cannot be neglected. This study aimed to uncover the benthic animal biodiversity of the Servemar X and Vapor de Baixo shipwrecks, located on the coast of Pernambuco State, Brazil, to reveal the importance of these artificial environments for hard substrata benthic fauna. They are sunk about 8.8 km from each other and settled on the sandy bottom at an average depth of 23 m. During the period of December 2005 to February 2007, the shipwrecks were visited to collect biological data. Organisms were identified with the aid of relevant bibliography (at a specific level when possible) or sent for identification by specialists when necessary. A total of 57 taxa were identified, of which 41 were found on Vapor de Baixo and 29 on Servemar X. The benthic macrofauna included eight phyla: Porifera (Demospongiae), Cnidaria (Hydrozoa and Anthozoa), Mollusca (Bivalvia and Gastropoda), Annelida (Polychaeta), Arthropoda (Cirripedia), Bryozoa (Cheilostomata), Echinodermata (Asteroidea and Echinoidea), and Chordata (Ascidiacea). Only 34.6% of the species were common to both shipwrecks. Biodiversity was considered compatible when compared with other shipwrecks located from the Brazilian coast and other locations. Regarding the species distribution in Brazil, eight new occurrences were recorded for Pernambuco: two reports for northward distribution expansion (Obelia dichotoma and Celleporaria atlantica), two southward (Spondylus erinaceus and Didemnum duplicatum), and another four species that closed their distributional hiatus in the Northeast Region (Aetea sica, Hippaliosina imperfecta, Stylopoma informata and Trididemnum orbiculatum). The shipwrecks that serve as artificial reefs in shallow waters of Pernambuco may contribute to the success of larvae that were previously being lost due to the scarcity of appropriate substrates on which to settle.